Irradiated Beetroot Extract as a Colorant for Cream Cheese - Junqueira-Conceicao Goncalve, M (2011)
A Brazilian ham-flavored cream cheese was developed using gamma-irradiated beetroot extract as the colorant. An irradiation dose of 5.0 kGy was used based on previous studies that indicated no growth of moulds, yeasts and aerobic psychotropic microorganisms during 12 days at 5. °C, and with no changes in the structure of the pigment. One part of the cheese was colored with the irradiated beetroot extract and the other part with carmine cochineal, which is a natural stable colorant but expensive and difficult to extract. Both portions were submitted to sensory evaluation with 67 panelists. No significant differences were found in flavor and overall appearance. The cream cheese containing carmine cochineal was slightly preferred in regards to color. However, being a new product, these results were encouraging and point towards the potential use of irradiated beetroot extract as a natural food colorant. © 2010 Elsevier Ltd.